Outpatient treatment of worsening heart failure with intravenous and subcutaneous diuretics: a systematic review of the literature - Eric Wierda; Cathelijne Dickhoff; Martin Louis Handoko; Liane Oosterom; Wouter Emmanuel Kok; Y. deRover; B.A.J.M. deMol; Loek vanHeerebeek; Jutta Maria Schroeder‐Tanka (ESC Heart Failure)
Abstract Aims In the coming decade, heart failure (HF) represents a major global healthcare challenge due to an ageing population and rising prevalence combined with scarcity of medical resources and increasing healthcare costs. A transitional care strategy within the period of clinical worsening of HF before hospitalization may offer a solution to prevent hospitalization. The outpatient treatment of worsening HF with intravenous or subcutaneous diuretics as an alternative strategy for hospitalization has been described in the literature. Methods and results In this systematic review, the available evidence for the efficacy and safety of outpatient treatment with intravenous or subcutaneous diuretics of patients with worsening HF is analysed. A search was performed in the electronic databases MEDLINE and EMBASE. Of the 11 included studies 10 were single‐centre, using non‐randomized, observational registries of treatment with intravenous or subcutaneous diuretics for patients with worsening HF with highly variable selection criteria, baseline characteristics, and treatment design. One study was a randomized study comparing subcutaneous furosemide with intravenous furosemide. In a total of 984 unique individual patients treated in the reviewed studies, only a few adverse events were reported. Re‐hospitalization rates for HF at 30 and 180 days were 28 and 46%, respectively. All‐cause re‐hospitalization rates at 30 and 60 days were 18–37 and 22%, respectively. The highest HF re‐hospitalization was 52% in 30 days in the subcutaneous diuretic group and 42% in 30 days in the intravenous diuretic group. Conclusions The reviewed studies present practice‐based results of treatment of patients with worsening HF with intravenous or subcutaneous diuretics in an outpatient HF care unit and report that it is effective by relieving symptoms with a low risk of adverse events. The studies do not provide satisfactory evidence for reduction in rates of re‐hospitalization or improvement in mortality or quality of life. The conclusions drawn from these studies are limited by the quality of the individual studies. Prospective randomized studies are needed to determine the safety and effectiveness of outpatient intravenous or subcutaneous diuretic treatment for patient with worsening HF.